Legal Wisdom in Indonesian Legal System: Toward Progressive Law Enforcement - Muhammad Ridwan Hidayat; Suteki, Suteki; Jean Claude Geofrey Mahoro (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This study aims to analyze the state of society that began without a system, or what is called the condition of disorder, which is unstable (social melee) so that the state of law, when it comes to people's lives, must also follow the unstable pattern (legal melee). The method used is normative philosophical, which leads to the basis of discourse (Conceptual). This study also explains some of the gaps in previous similar studies by presenting some novelty of analysis, such as (1) an explanation of how legal wisdom is an important concept for progressive law enforcement, (2) the national legal system (conventional) with legalistic positivistic substance remains an open formulation towards legal progressiveness in Indonesia. The exposure of the construction of a legal system continuously undergoing development is an issue that must always get a balance for new legal discoveries so that the developing law always follows the development of society. The results of this study revealed that the existing legal products also naturally show how the law plays a role. Then, with the existence of legal products, one area that gets regulation against it must be more organized than areas that legal arrangements have not been regulated by law. It can be concluded that today's Indonesian legislation is a portrait that shows the problem of existing regulations. It has become natural to revive and develop with a more structured of legal enforcement.